Social and Economic Processes Management at the Enterprise on an Innovative Basis. (Economics and region, 2018)
The essence of the concept of «socio-economic processes» is considered. The main tasks and features of management of social and economic processes at the domestic enterprises are highlighted. Effective methods of managing economic processes at the enterprise are determined (taking into account the practice of foreign countries). The peculiarities of management of socio-economic processes of the enterprise on the innovative basis are investigated.
Keywords: economic potential; economic process; innovations; innovation process; social sphere; socio-economic processes; competitiveness; enterprise; management